2019
DOI: 10.32606/ijsr.v10.i1.00028
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficiency Of Various Substrates And Supplements On Growth Behaviour And Yield Potential Of Pleurotus flabellatus

Abstract: An experiment was conducted to study the comparative efficiency of various substrates viz, wheat straw (Triticum aestivum l.), paddy straw (Oryza sativa l.), corn stalk (Zea mays l.) and typha leaves (Typha angustifolia) and different supplements such as wheat bran, rice bran, neem cake and fenugreek bran on growth behavior and yield potential of oyster mushroom (pleurotus flabellatus). In these investigations higher mushroom yield with biological efficiency (BE) of 86.6 percent was obtained from wheat straw f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Khare et al (2007) observed that the species P. sajor caju and P. florida grown on wheat straw substrates supplemented with grain flour, wheat bran increased yield of the mushroom as compared to control. Gautam and Ram (2007) studied the effect of wheat straw and different supplements such as wheat bran, Rice bran on growth behavior and yield potential of Oyster mushroom.…”
Section: Moisture Contentmentioning
confidence: 99%
“…Khare et al (2007) observed that the species P. sajor caju and P. florida grown on wheat straw substrates supplemented with grain flour, wheat bran increased yield of the mushroom as compared to control. Gautam and Ram (2007) studied the effect of wheat straw and different supplements such as wheat bran, Rice bran on growth behavior and yield potential of Oyster mushroom.…”
Section: Moisture Contentmentioning
confidence: 99%